## Find the inference rule of the given functional dependency / Armstrong's axioms / Inference rules / Normalization process

####
**Question:**

**1. For a relation R(A, B, C), if A → B and A → C holds, then A → BC also holds. Which of the following rule ensures this?**

(a) Augmentation rule

(b) Union rule

(c) Decomposition rule

(d) None of the above

####
**Answer:**

**(b) Union rule**

*Union rule says that a set of functional dependencies that have same left hand side attributes can be combined to form a single functional dependency. For example, the FDs AC → B, AC → DE and AC → F can be combined to AC → BDEF.*

Decomposition rule is the opposite of union rule. Augmentation rule is about adding same set of attributes on both sides of a functional dependency.

## No comments:

## Post a Comment